Integration Of Philosophy in The Modern National Education Curriculum - Aini, Kusuma Dewi Nur; Pamungkas, Catur Bayu; Fatahillah, Rahhmanda Aqsa (Journal of Multidiscipline and Collaboration Research, 2025)
This research aims to analyze the importance of the integration of philosophy in the national education curriculum, focusing on its contribution in shaping a more holistic and character-building oriented education. The method used is qualitative research with a descriptive-analytical approach to library research, analyzing literature from figures in the philosophy of education such as John Dewey, Paulo Freire, and Syed Naquib al-Attas, as well as global education policy reports. The findings of this study show that philosophy has an important role in directing the educational curriculum, not only in the development of cognitive competence, but also in the formation of students' morals and ethics. This study found that the integration of philosophy in the curriculum can overcome the problem of fragmentation of values and the inalignment of educational goals with social realities. The results of this study underscore the need for a more critical, reflective and value-based approach to the curriculum, which not only meets the demands of the job market, but also shapes socially responsible and ethical individuals. This research makes a significant contribution to educational reform by providing a theoretical basis for the development of a curriculum that is more comprehensive and relevant to the challenges of the times.